THE EFFECT OF FUNDING AND RISK ON FINANCING DECISION Empirical Study of Islamic Banks in Indonesia - Sutrisno, Sutrisno (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2016)
The purpose of this study was to analyze the effect of funding decisions and risk to financing decisions on Islamic banking in Indonesia. Funding decisions consists of variable wadia demand deposits (GWD), mudaraba saving deposit (TAB), and mudaraba time deposits (DEP). Risk is proxied by capital risk (CAR), liquidity risk (RR and FDR), and financing risk (NPF). While the financing decisions consists of murabaha financing, mudaraba financing, and Musharaka financing. Samples were taken from all Islamic banks operating in Indonesia by 11 Islamic banks, and quarterly data using multiple regression analysis. The results showed that DEP and TAB significant and positive impact on all of financing, while GWD significant and positive impact on murabahafinancing is however negatively affect to mudaraba and musharaka financing. CAR and RR a significant and negative effect on all of financing. NPF non significant effect on all financing decisions, while FDR significant and negative effect on mudaraba and musharaka financing, but no significant effect on murabaha financing